Voluntary Sector Participation and Support for Redistribution: Evidence From 18 Advanced Industrial Democracies (1990–2013). (April 2023) - Sealey, Anthony; Handy, Femida
The governments of the advanced industrial democracies have long provided public policies that redistribute income, and public support for such redistribution has varied across countries and over time. "Who is likely to support these egalitarian policies?" is a perennial question. This article investigates individuals' participation in voluntary sector organizations (VSO) to understand the relationship between VSO participation and support for public policies aimed at reducing inequalities. We use five waves of the World Values Survey across 18 advanced industrial democracies to examine this relationship. Our findings suggest that, in aggregate, the impact of VSO participation negatively influences support for redistribution. This pattern of support changes significantly, however, when we consider the type of VSO, suggesting that VSO participation is not homogeneous. Individuals' support for redistribution is conditioned by where their VSO participation happens.